STRATEGI MARKETING PUBLIC RELATIONS MELALUI MEDIA SOSIAL DALAM MEMBANGUN BRAND AWARENESS - Eva Nuraeni; Ari Pandu Witantra; Andin Nesia (Universitas Sultan Ageng Tirtayasa, 2024)
This research is motivated by the increasing development of technology which can now make the work of a Public Relations person easier, by utilizing social media. To build Brand Awareness, the right strategy is needed. This research aims to find out how Marketing Public Relations Strategy through social media builds Brand Awareness (Study on the official Instagram account@nasikulitmalamminggu) This research uses Marketing Public Relations and is supported by the Three ways Strategy concept from Thomas L. Harris (1991). This research is descriptive qualitative in nature, using a case study method, data collection techniques through in-depth interviews, observation and documentation. The results of this research show that the marketing public relations strategy carried out by Nasi kulit Malam Minggu is: Pull strategy, actively publish via social media Instagram regarding activities that are being carried out, provide several promotions and actively collaborate with various well-known brands. Special event Push Strategy participated in the IFRA 2023 exhibition, providing endorsements to several influencers. Pass strategies through Corporate Social Responsibility (CSR) activities in collaboration with the community.Keywords: Brand awareness, Marketing Public Relations, Nasi Kulit Malam Minggu